What's the Original Concept of Meridian and Acupuncture Point in Oriental Medicine? - A Perspective of Medical History - YIN Chang- Shik; KOH Hyeong- Gyun (Uisahak, 2005)
Meridian and acupuncture point(MAP) is a core theory of acupuncture and essential building blocks of oriental medicine. There still continue theoretic or experimental arguments and controversies on the origination or original concept of MAP, without any definite approval or disapproval of a hypothesis. The theory of MAP is an historic product and has never been outside of historic influences. This study discusses the original concept of meridian and acupuncture point theory and its historical evolution, based on the review of classic literatures on meridian including the mawangdui medical texts of Han dynasty. The concept of MAP served as a empirical reference system in clinical settings irrespective of the anatomical entity of MAP.